PENERAPAN STRATEGI CITY BRANDING DALAM MEWUJUDKAN SUBULUSSALAM SEBAGAI KOTA SANTRI - Padang, Faisal; Husna, Asmaul; Fahrimal, Yuhdi (Program Studi Ilmu Komunikasi Universitas Komputer Indonesia, 2021)
City Branding is an idea about how the city builds and communicates its character, attractiveness, style, and personality by using a visual identity, tagline, exhibition, and positioning that are effective and relevant to their public target. By using Kavaratzis’s city branding concept with descriptive qualitative method, this article tries to explore the implementation of Subulussalam’s city branding in an effort to realize the Kota Santri. The results of this study found that the strategy that has been implemented in the last two years has gone through five main stages, such as research, deliberation, consultation, action, and communication. The obstacles faced are inadequate planning, insufficient budget, lack of use of technology, and inadequate monitoring and evaluation processes in this strategy.